Fundamentals of financial management - Brigham, Eugene F. (The Dryden Press, 1995)
This book's unique balance of clear concepts, contemporary theory, and practical applications helps readers better understand the concepts and reasons behind corporate budgeting, financing, and working capital decision making. Numerous practical examples, proven end-of-chapter applications, and Integrated Cases demonstrate theory in action, while Excel Spreadsheet Models help readers master this software tool. It's a book designed to put each reader first in finance today.